2016
DOI: 10.1016/j.freeradbiomed.2015.12.019
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant supplementation accelerates cachexia development by promoting tumor growth in C26 tumor-bearing mice

Abstract: More than 50% of patients with advanced stages of colon cancer suffer from progressive loss of skeletal muscle, called cachexia, resulting in reduced quality of life and shortened survival. It is becoming evident that reactive oxygen species (ROS) regulate pathways controlling skeletal muscle atrophy. Herein we tested the hypothesis that antioxidant supplementation could prevent skeletal muscle atrophy in a model of cachectic Colon 26 (C26) tumor-bearing mice. Seven-week-old BALB/c mice were subcutaneously ino… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
38
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 50 publications
(43 citation statements)
references
References 54 publications
5
38
0
Order By: Relevance
“…Cachectic C26 mice exhibited a net augmentation in protein carbonyls and 4-HNE content within plasma, without any change in skeletal muscle. The absence of muscular oxidative damage in our model could be attributed to the upregulation of catalase expression, exclusively, in atrophied muscles [17]. Other experimental studies have also shown that mice bearing Walker 256 and MAC13/16 tumors developed cardiac cachexia in response to DNA and/or protein oxidative damage in heart tissues [20, 36].…”
Section: Multiorgan Presence Of Oxidative Stress Markers During Camentioning
confidence: 84%
See 3 more Smart Citations
“…Cachectic C26 mice exhibited a net augmentation in protein carbonyls and 4-HNE content within plasma, without any change in skeletal muscle. The absence of muscular oxidative damage in our model could be attributed to the upregulation of catalase expression, exclusively, in atrophied muscles [17]. Other experimental studies have also shown that mice bearing Walker 256 and MAC13/16 tumors developed cardiac cachexia in response to DNA and/or protein oxidative damage in heart tissues [20, 36].…”
Section: Multiorgan Presence Of Oxidative Stress Markers During Camentioning
confidence: 84%
“…A previous study demonstrated that nuclear factor- κ B (NF- κ B) was rapidly activated by H 2 O 2 , following treatment of C2C12 muscle cells with TNF- α [10]. We have also shown that circulating levels of TNF- α were increased in cachectic mice bearing colon tumor and coincided with a greater phosphorylation of the NF- κ B (p65) subunit, within atrophied muscles [17]. The nuclear accumulation of NF- κ B promotes the transcriptional upregulation of muscle-specific E3 ubiquitin-ligases, MuRF-1 and MAFbx , which in turn tag myofibrillar proteins (i.e., myosin) with polyubiquitin chains for proteasome processing [52].…”
Section: Ros Production and Inflammation: Causality Link And Princmentioning
confidence: 99%
See 2 more Smart Citations
“…Vitamin E may help prevent CIPN. l-glutamine, goshajinkigan, and omega-3 are also promising in the prevention of the effects of CIPN [7].…”
Section: Cancer Treatmentmentioning
confidence: 99%